PENYULUHAN SLOW DEEP BREATHING UNTUK MENURUNKAN HIPERTENSI PADA KOMUNITAS LANSIA DI POSYANDU BANDULAN KOTA MALANG: SLOW DEEP BREATHING COUNSELING TO REDUCE HYPERTENSION IN THE ELDERLY COMMUNITY AT POSYANDU BANDULAN, MALANG CITY - Nur Atiqatul Himmah; Gamar Gamar; Ali Multazam (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Hypertension is a high blood pressure disease that often occurs in the elderly. The incidence of hypertension in Indonesia is very high. With education, you can increase knowledge of hypertension so that it can reduce the incidence of hypertension. Outreach activities are carried out to educate the elderly about hypertension such as signs of symptoms, how to prevent it and how to reduce high blood pressure with slow deep breathing exercises which can be done at home. This method uses health promotion about hypertension to the elderly at Posyandu Bandulan Malang City using poster media. Before counseling, the elderly had their blood pressure checked first, then the elderly were gathered to be given a pretest about hypertension and then given counseling material about hypertension. Then a slow deep breathing demonstration was carried out, at the end of the activity a posttest was carried out with questions and answers to measure understanding after giving the material. The results of this activity showed an increase in understanding of the definition, signs and symptoms of hypertension with the percentage before counseling increasing from 10% to 100%. The percentage of understanding regarding the prevention and causes of hypertension before counseling was 5% and increased to 100%. And the understanding of slow deep breathing exercise obtained before counseling from 0% increased to 100%. This activity increases the elderly's understanding of hypertension, the elderly can understand and do breathing exercises, namely slow deep breathing to lower.